Establishment and characterization of a new cell line (SSP-9) derived from Atlantic salmon Salmo salar that expresses type I ifn - Rodríguez Saint-Jean, Sylvia; González, C.; Monrás, Mónica; Romero Jódar, Alejandro; Ballesteros, Natalia; Enríquez, Ricardo; Pérez Prieto, Sara I. (Journal of Fish Biology, 2014)
In the present work, the establishment and biological characterization of a new cell line, SSP-9, derived from the pronephros of the Atlantic salmon Salmo salar, are reported. These cells grew well in Leibovitz's (L15) medium supplemented with 10% foetal calf serum at temperatures from 15 to 25° C, and they have been sub-cultured over 100 passages to produce a continuous cell line with an epithelial-like morphology. The SSP-9 cells attached and spread efficiently at different plating densities, retaining 80% of cell viability after storage in liquid nitrogen. When karyotyped, the cells had 40-52 chromosomes, with a modal number of 48. Viral susceptibility tests showed that SSP-9 cells were susceptible to infectious pancreatic necrosis virus and infectious haematopoietic necrosis virus, producing infectious virus and regular cytopathic effects. Moreover, these cells could be stimulated by poly I:C, showing significant up-regulation in the expression of the genes that regulate immune responses, such as ifn and mx-1. SSP-9 cells constitutively express genes characteristic of macrophages, such as major histocompatibility complex (mhc-II) and interleukin 12b (il-12b), and flow cytometry assays confirmed that SSP-9 cells can be permanently transfected with plasmids expressing a reporter gene. Accordingly, this new cell line is apparently suitable for transgenic manipulation, and to study host cell-virus interactions and immune processes. This work was funded by the Ministerio de Economía y Competitividad (MINECO), Spain (grant AGL-2010-18454), by the Consejo Superior de Investigaciones Cientificas (CSIC: grant E2010-20E084) and by Fondecyt, Chile (grant 2008-1080571) and grant FONDEF DO2I 1122. The authors wish to thank M. Sánchez and L. Guaita for their excellent technical assistance. N.B. wants to thank the MINECO for the award of a PhD student fellowship.